The Methodology for the Formation of the Regional Food-producing Clusters - Dotdueva, Zukhra S.; Gorlov, Sergei M.; Marchenko, Ekaterina V.; Takhumova, Oksana V.; Kaverzin, Sergei A.; Sugaipova, Irina V. (International Review of Management and Marketing, 2016)
The cluster conception represents a relatively new approach to the regional organization of the economic system focusing on the relationships among companies and the existence of clusters in the interrelated industries (Karepova et al., 2015). The efficiency of cluster formation in different economic sectors is achieved through the combination of geographical location of interrelated companies and joint efforts of business, government and science (Ryazantsev et al., 2015). It has been proved in practice that the cluster organization of regional economies leads to the increase in labour and production efficiency as well as reduces transactional expenses and encourages innovations (Pismennaya et al., 2015). During the period of the economic reforms implementation, the agricultural companies of the country were left with no state support; they had to face high prices for resources as well as the mass purchase of agricultural products by unscrupulous sub-purchasers and the absence of any appropriate market infrastructure. Keywords: regional system, market mechanism, agro-industrial sector, fruit market, clustering, development model JEL Classifications: L66, R15, M49